The Anguilliform eels (Pisces Anguilliformes) of Bago River and Adjacent waters in Negros Occidental, Philippines - Bucol, Abner A.; Menes, Carmen; Linaugo, Joji D.; Pacalioga, Jessica O. (2010)
The Eels (Order Anguilliformes) occurring in Bago River and adjacent waters in Negros Occidental, Philippines are briefly annotated. A total of 21 species in six families are included in this paper. Snake-eels (Ophichthidae) consists of 11 species, Conger Eels (Congridae) are represented by three species, while only two species belong to the family Muraenesocidae and the Freshwater Eels (Anguillidae) and Spaghetti Eels (Moringuidae) are each represented by a single species.
Keywords: Eels; Freshwater biodiversity; Negros Occidental